Effect of lectin (ScLL) on fibroblasts stimulated with LPS - an in vitro study - Manuella Verdinelli de Paula REIS; Camilla Christian Gomes MOURA; Marcus Vinicius da SILVA; Maria Aparecida de SOUZA; Priscilla Barbosa Ferreira SOARES; Carlos José SOARES
Abstract: The lectin (ScLL) extracted from the Synadenium carinatum plant has been evaluated as an immunomodulator in diseases such as asthma, neosporosis and leishmaniasis. However, it has not yet been evaluated in the oral cavity. This study evaluated the effect of ScLL on viability, proliferation and release of IL-10 in human gingival fibroblasts (HGF) stimulated with lipopolysaccharide (LPS). HGF were stimulated with LPS 1 µg/ml and treated with ScLL in concentrations of 10, 5 and 2 µg/ml for 1 and 5 h, and evaluated by flow cytometry for viability, apoptosis (initial/advanced) and necrosis. The supernatant was collected to detect release of IL-10 by ELISA. The proliferation was assessed with the BrdU assay. Positive control consisted of cells maintained in Dulbecco's Modified Eagles Medium (DMEM), and the negative control, of those kept in tap water. Data were analyzed by ANOVA and Dunnett's test (α = 0.05). No significant difference was found for ScLL concentrations regarding viability or initial and advanced apoptosis (p=0.455). All the groups, including the positive control, had a significantly lower necrosis parameter than negative control at 5 h (p < 0.001). No difference was found for proliferation among the experimental groups (p = 0.832). ScLL at 5 and 2 µg/ml resulted in a lower release of IL-10 than positive and negative controls at 5 h (p = 0.047). The results indicated that ScLL concentrations tested were not cytotoxic, and had no effect on proliferation and release of IL-10 parameters. A thorough understanding of ScLL, regarding its immunomodulatory potential, may open the door to new perspectives for dentistry.